2013
DOI: 10.1111/j.1469-0691.2012.03903.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of Staphylococcus aureus bloodstream infection: a multinational population-based surveillance study

Abstract: Although the epidemiology of Staphylococcus aureus bloodstream infection (BSI) has been changing, international comparisons are lacking. We sought to determine the incidence of S. aureus BSI and assess trends over time and by region. Population-based surveillance was conducted nationally in Finland and regionally in Canberra, Australia, western Sweden, and three areas in each of Canada and Denmark during 2000-2008. Incidence rates were age-standardized and gender-standardized to the EU 27-country 2007 populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
159
3
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(198 citation statements)
references
References 33 publications
21
159
3
15
Order By: Relevance
“…Overall, these data support the estimate that the contemporary incidence of community-onset Staphylococcus aureus BSI is approximately 15 per 100,000 in Western countries and is associated with a 30-day all-cause case fatality rate of 20% and a mortality rate of 3 per 100,000 (107). Notably, MRSA strains vary widely internationally, and in some cases MRSA appears to add to and in others replaces the burden due to methicillin-sensitive S. aureus (MSSA) (85).…”
Section: Specific Etiologiessupporting
confidence: 80%
See 1 more Smart Citation
“…Overall, these data support the estimate that the contemporary incidence of community-onset Staphylococcus aureus BSI is approximately 15 per 100,000 in Western countries and is associated with a 30-day all-cause case fatality rate of 20% and a mortality rate of 3 per 100,000 (107). Notably, MRSA strains vary widely internationally, and in some cases MRSA appears to add to and in others replaces the burden due to methicillin-sensitive S. aureus (MSSA) (85).…”
Section: Specific Etiologiessupporting
confidence: 80%
“…Staphylococcus aureus is the second most common species causing BSI in population-based studies, and there is an evolving body of literature focusing specifically on this pathogen (2,6,8,9). Table 4 displays studies investigating the burden of community-onset Staphylococcus aureus BSI in nonselected populations (63,(82)(83)(84)(85)(86). Several other population-based studies, in addition to those presented in Table 3, have been reported but either had older or duplicative data with tabulated studies (87)(88)(89)(90), were limited to subgroups such as MRSA only (91)(92)(93)(94), included selected age groups (95-101), or did not report or clearly differentiate between community-and hospital-onset disease (102)(103)(104)(105)(106).…”
Section: Specific Etiologiesmentioning
confidence: 99%
“…In the industrialized world, the population incidence of SAB ranges from 10 to 30 per 100,000 person-years (7). Longitudinal data from Denmark provide considerable insight into the impact of changes in access to health care interventions on SAB incidence.…”
Section: Epidemiologymentioning
confidence: 99%
“…29 Community-acquired MRSA infections have emerged as a global problem since the turn of the 21 st century. [30][31][32] Five major clones are found to be associated with most of the CA-MRSA infections worldwide including multilocus sequence type 1 (ST-1)/USA400 and ST-8/USA300 dominantly found in North America, ST-59 observed in South East Asia, ST-80 observed in Europe and ST-30 distributed worldwide 28 . The clonal structure remains to be determined in CAESAR countries.…”
Section: Gram-positive Bacteriamentioning
confidence: 99%